Hyperostosis associated with prostaglandins. Report of three cases (2013)
We present a series of cases of patients with reactive hyperostosis secondary to prolonged use of prostaglandins in the context of complex congenital heart disease, which due to its hemodynamic condition required to maintain the left to right vascular shunt for their survival. We show the typical imaginological characteristics in conventional radiography and discuss the pathophysiological details and the differential diagnoses.